2006
DOI: 10.1161/01.atv.0000234978.10658.41
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin/Cyclic AMP Pathway Induces Notch Activation and Differentiation of Arterial Endothelial Cells From Vascular Progenitors

Abstract: Objective— The acquisition of arterial or venous identity is highlighted in vascular development. Previously, we have reported an embryonic stem (ES) cell differentiation system that exhibits early vascular development using vascular endothelial growth factor (VEGF) receptor-2 (VEGFR2)-positive cells as common vascular progenitors. In this study, we constructively induced differentiation of arterial and venous endothelial cells (ECs) in vitro to elucidate molecular mechanisms of arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 45 publications
3
122
1
Order By: Relevance
“…Yurugi-Kobayashi et al 17 did not report upregulation of arterial genes without cAMP activation, keeping in mind that they examined gene expression one day earlier compared with this study. FACS analysis show that CD31 ϩ cells at 6, 7, and 8 days of differentiation incorporate acetylated-LDL with high specificity indicative of functional endothelial population, allowing us to dissect the temporal linage commitment.…”
Section: Vegf Is Required For Endothelial Differentiation and Controlmentioning
confidence: 60%
See 1 more Smart Citation
“…Yurugi-Kobayashi et al 17 did not report upregulation of arterial genes without cAMP activation, keeping in mind that they examined gene expression one day earlier compared with this study. FACS analysis show that CD31 ϩ cells at 6, 7, and 8 days of differentiation incorporate acetylated-LDL with high specificity indicative of functional endothelial population, allowing us to dissect the temporal linage commitment.…”
Section: Vegf Is Required For Endothelial Differentiation and Controlmentioning
confidence: 60%
“…16 Using a similar approach Yurugi-Kobayashi et al recently found arterial specification to be critically dependent on Adrenomedullin-activated cAMP. 17 Our study shows a dual function for VEGF as a determinant of endothelial cell fate but also as a dose dependent inducer of lineage specificity. Blocking Notch signaling inhibited VEGF-induced arterial specification and promoted venous identity without effecting de novo endothelial cell formation.…”
mentioning
confidence: 67%
“…When Flk1 + hematopoieticendothelial progenitors isolated from differentiation cultures are re-differentiated in the presence of VEGF, lineages of both endothelial cells and mural cells (pericytes and vascular smooth muscle) develop from a common [46,47]. Endothelial differentiation has also been demonstrated in human ES cell differentiation cultures [48] We have been studying the roles of TGF-β family signals during vascular development from mouse ES cells.…”
Section: Mesoderm Derivativesmentioning
confidence: 99%
“…3 Indeed, arteriovenous (AV) specification of ECs is accomplished early in development and is associated with the expression of a specific complement of factors: venous endothelium is characterized by the expression of EphB4, 4 Lefty-1, 5 Lefty-2, 5 COUP-TFII, 6 and MYO1-␤, 5 and arterial ECs express high levels of Notch 1 and 4, 7 Dll-4, 8 EphrinB1 and EphrinB2, 4 Jagged-1 and -2, 7 connexin-40, and Hey-2 (gridlock zebrafish ortholog). 9,10 Studies in Xenopus, zebrafish, and mice have revealed that, besides blood flow, 11 vessel-intrinsic cues and-later in development-signals from outside the vasculature 12,13 are implicated in defining arterial or venous fate such as members of the TGF-␤ pathway, 14,15 VEGF isoforms, 13,[16][17][18] neuropilins, 17 angiopoietins, 19 the Notch pathway, 7,9,[20][21][22] the patched pathway, 20 and COUP-TFII, a member of the orphan nuclear receptor superfamily. 6 Although it has been shown that some of these pathways are well conserved from zebrafish to mouse, less information is available on whether they have a similar role in humans.…”
Section: Introductionmentioning
confidence: 99%